Flowering phenology and pollen characteristics of cultivated populations of Paeonia ostii ‘Feng dan’ at different altitudes - Li, Xinwei; Li, Ting; Shao, Yuru; Ma, Haoang; Hou, Xiaogai; Qiao, Qi (Ciência rural, 2024)
From a pollination biology standpoint, this study compared modifications in the flowering phenology, soluble sugar and protein content of pollen, antioxidant enzyme system, and storage traits of five cultivated populations of Paeonia ostii ‘Feng dan’ at various altitudes in Luoyang. The findings indicated that the first blooming phase was delayed at greater altitudes. There was a significant difference in the soluble sugar content of pollen between sites; and there was no discernible relationship between soluble sugar content and altitude. With increasing altitude, there is a tendency for soluble protein content to decrease. The activities of antioxidant enzymes in pollen from cultivated populations at varying altitudes showed SOD and POD enzyme activities generally increasing with decreasing temperature, whereas CAT enzymes showed divergent patterns. Differences existed in the storage time of pollen across populations at different altitudes, and pollen from higher altitudes appeared to be better adapted to low-temperature storage environments. The rate of decrease in pollen viability under dry storage at -74.7 °C was significantly lower than under other storage conditions. The comprehensive analysis concludes that the variations in ‘Feng dan’ cultivation populations within the same region at different altitude zones can be leveraged for cross-pollination among proximate populations, utilizing low-temperature dry pollen storage technology, with the aim of achieving abundant oil peony production. RESUMO: Neste estudo, compararmos a fenologia da floração, os açúcares solúveis e as proteínas solúveis do pólen, as enzimas antioxidantes e as características de armazenamento de cinco populações cultivadas de Paeonia ostii ‘Feng dan’ em diferentes altitudes em Luoyang, na perspectiva da biologia da polinização. O pólen é um fruto de uma espécie de árvore, com um teor de proteínas solúveis e de pólen, sistema de enzimas antioxidantes e características de armazenamento. Os resultados mostraram que o início da floração foi mais tardio em altitudes mais elevadas. O teor de açúcar solúvel do pólen variou significativamente entre diferentes locais, não havendo uma relação óbvia com a altitude, enquanto o teor de proteínas solúveis tendeu a diminuir com o aumento da altitude. As atividades das enzimas antioxidantes do pólen de populações cultivadas a diferentes altitudes diferiram entre si, as atividades das enzimas SOD e POD aumentaram basicamente com a diminuição da temperatura, enquanto a enzima CAT apresentou várias tendências. Verificaram-se diferenças no tempo de armazenamento do pólen de populações de diferentes altitudes, e o pólen de populações de altitudes mais elevadas parecia estar mais bem adaptado a ambientes de armazenamento a baixas temperaturas. A taxa de redução da viabilidade do pólen sob armazenamento seco a -74,7 °C foi significativamente menor do que sob outras condições de armazenamento. As análises sugerem que as diferenças entre as populações de cultivo de ‘Fengdan’ na mesma região a diferentes altitudes podem ser exploradas para efetuar a polinização cruzada entre populações próximas, utilizando a tecnologia de armazenamento de pólen por secagem a baixa temperatura, com vista a atingir o objetivo de produção abundante e em grande escala de peónia oleaginosa.